Keefektifan Model Problem Based Learning dengan Video Perubahan Wujud Benda untuk Meningkatkan Keterampilan Berpikir Kritis - Yuri Supriyono; Joko Siswanto; Iin Purnamasari (Jurnal Kualita Pendidikan, 2022)
This research is motivated by the low critical thinking ability of students, one of which is the use and selection of inappropriate learning models. Researchers used the Problem Based Learning model with videos of changes in the shape of objects. This study aims to determine the effectiveness of the Problem Based Learning model with videos of changing the shape of objects to improve students' critical thinking skills. The research method used is Quasi Eksperimental Design, the sampling of this research uses 2 study groups totaling 12 students for the Experiment class and 12 students for the Control class. The instrument in this study used a test of students' critical thinking skills in the form of questions, namely pretest and posttest. The variables in this study consisted of the independent variables of the Problem Based Learning model with videos of changes in the shape of objects and the dependent variable was the ability to think critically. The data analysis method was carried out by applying the Independent Sample t-test to test the hypothesis and the N-Gain test to assess the effectiveness of the learning model. Independent Sample t-test obtained sig. (2-tailed) of 0.004 <0.05, it is concluded that there is an influence or Ho is rejected and H1 is accepted. The results of the effectiveness analysis using the N-Gain test obtained a score of 0.4922, meaning that the level of effectiveness of the Problem Based Learning model with changes in the shape of objects in the experimental class is included in the medium category.